Comparative Study of Natural (Lactic Acid) and Synthetic (Pyodine) Antiseptic Teat Dips for Mastitis Control in Dairy Cattle (Journal of Agriculture and Veterinary Science, 2026)
Bovine mastitis is one of the most economically important diseases affecting dairy cattle worldwide, leading to reduced milk yield, altered milk composition, and increased treatment costs. The present study aimed to evaluate the effectiveness of natural and synthetic antiseptic solutions used for post-milking teat dipping to control subclinical mastitis in dairy cows and to assess their economic feasibility. A total of 20 lactating dairy cows with healthy udders were selected and randomly divided into five groups (n = 4 cows per group). Group G-1 served as the control, while G-2 and G-3 received lactic acid teat dip solutions at concentrations of 2% and 5%, respectively. Groups G-4 and G-5 received synthetic antiseptic pyodine solutions at concentrations of 2% and 5%, respectively. The experiment lasted 28 days. Milk samples were collected weekly and screened for subclinical mastitis using the California Mastitis Test (CMT) and Surf Field Mastitis Test (SFMT). The results indicated that the highest incidence of mastitis occurred in the control group (G-1), followed by G-4, G-2, and G-5, whereas no cases of subclinical mastitis were recorded in the G-3 group during the entire experimental period. The economic evaluation showed that pyodine-based solutions were less expensive than lactic acid solutions. However, the 5% lactic acid treatment demonstrated superior efficacy in reducing subclinical mastitis. The findings suggest that lactic acid teat dipping can serve as an effective natural alternative for mastitis control in dairy cattle, although further studies with larger sample sizes are recommended.